Correlation of lipid profile of infertile men with abnormal semen parameters - Singh, Lovely; Bajaj, Bindu; Monika; Rani, Kumari Usha; Panwar, Megha; Ranga, Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Male’s inability to impregnate a fertile female is referred as male factor infertility. It accounts for 40-50% of infertile couples and affects almost 7% of all men. Male comorbidities and conditions, which negatively affect men’s health, have been repeatedly associated with impaired reproductive functioning. Cholesterol is the main substrate for steroid synthesis and it plays crucial role in formation of sperm plasma membrane and thus in spermatogenesis, highlighting the role of serum lipids in male fecundity. Purpose of the study is to evaluate correlation lipid profile of male partners with abnormal semen parameters in infertile couples. Methods: A cross sectional study was carried out in the infertility clinic of a tertiary care hospital for over 18 months and 151 infertile men with abnormal semen parameters (as per WHO 2010 criteria) were enrolled. Evaluation of lipid profile was done and its relationship with abnormal semen parameters was analyzed. Results: Significant positive correlation was seen between LDL and Triglyceride with sperm concentration and total sperm count. However, significant negative correlation was seen between Triglyceride and sperm motility and TMSC. Total and progressive motility was found to be significantly associated with total cholesterol (p<0.05). Infertile men having higher total cholesterol were found to have better total and progressive motility compared to men with less total cholesterol. Conclusions: Our findings demonstrated that lipid profile has significant correlation with semen parameters, specifically sperm concentration, count and motility.